A forward analysis on the applicability of tracer breakthrough profiles in revealing the pore structure of tight gas sandstone and carbonate rocks. Issue 6 (30th June 2015) - Mehmani, Ayaz; Mehmani, Yashar; Prodanović, Maša; Balhoff, Matthew
Abstract We explore tracer breakthrough profiles (TBP) as a macroscopic property to infer the pore‐space topology of tight gas sandstone and carbonate rocks at the core scale. The following features were modeled via three‐dimensional multiscale networks: microporosity within dissolved grains and pore‐filling clay, cementation in the absence and presence of microporosity (each classified into uniform, pore‐preferred, and throat‐preferred modes), layering, vug, and microcrack inclusion. A priori knowledge of the extent and location of each process was assumed to be known. With the exception of an equal importance of macropores and pore‐filling micropores, TBPs show little sensitivity to the fraction of micropores present. In general, significant sensitivity of the TBPs was observed for uniform and throat‐preferred cementation. Layering parallel to the fluid flow direction had a considerable impact on TBPs whereas layering perpendicular to flow did not. Microcrack orientations seemed of minor importance in affecting TBPs.